IHTT report on Pisa - 2022 - Ismadiyorova Nafisaxon Ibroximjon qizi (Journal of Learning on History and Social Sciences, 2024)
This article explains the purpose of the decision of the Cabinet of Ministers of the Republic of Uzbekistan No. 997 of December 8, 2018 “On measures to organize international studies in the field of education quality assessment in the public education system”, PISA - 2022 the results and the content of the tasks presented in it are highlighted. A sample assignment is also provided.